Hubungan antara Happiness dengan Fear of Missing Out pada Dewasa Awal Pengguna Media Sosial di NTT - Saekoko, Priska P. M; Arianti, Rudangta (Penerbit Goodwood, 2024)
Purpose: The purpose of this study was to determine whether there is a relationship between happiness and FoMO in early adult social media users in NTT. Research methodology: This study used quantitative research methods with non-linear regression design. The study participants were 212 early adult men and women with an age range of 18-40 years who lived in NTT and were active on one social media or even more than one with a minimum period of 3 hours a day. Results: The results of the non-linearity regression test using the